Of place and playmaking: working with everyday city spaces through theatre and performance - Halligey, Alexandra (Department of Drama, 2018)
This thesis proposes theatre and performance as tools for understanding the relational emergence of city spaces. It responds to two related urban studies calls. The first is for fine-grained ethnographies of the everyday to learn what city spaces might be becoming in order to strategise how to support these becomings. The second falls under the ‘cultural turn’ in urban thinking: what artistic projects might offer an everyday urbanism. Through an everyday urban lens, the work asserts the performativity of daily actions in constructing space, but also the affectual qualities that daily city life produces. These affectually charged, spatial constructions through the interrelation of daily activity are what make spaces become places, places that are temporary and always evolving. This thesis draws a link between everyday placemaking practices and the artistic practice of playmaking to propose theatre and performance as a way of learning about city spaces, actively engaging with this knowledge and broadcasting it. It argues that theatre and performance staged in the sites it seeks to know and in concert with city dwellers has the capacity to facilitate an embodied, but reflective experience of what it is to be continually implicated as a city dweller in spatial – and therefore place – construction through daily actions. The work takes as its primary focus a year-long participatory theatre and performance project run in the Johannesburg inner city suburbs of Bertrams, Lorentzville and Judith’s Paarl, resulting in a ‘site-specific’ play performed in the streets of the area. The practical component to the study is contextualized within the broader landscape of Johannesburg public art interventions over the last 15 years and specifically in relation to two other Johannesburg-based participatory public art projects: Terry Kurgan’s Hotel Yeoville and a series of public art commissions managed by The Trinity Session. The research uses Tim Ingold’s notion of corresponding with materiality in order to know as a methodology in service of understanding cities through their relational construction. This phronetic approach – knowing through doing – is applied to interpreting Kurgan’s and The Trinity Session’s work and to both the making of the theatre project in Bertrams, Lorentzville and Judith’s Paarl and the writing of this thesis. The study takes place at the intersection between urban studies, theatre and performance studies and public art. It draws together the socially-engaged concerns and considerations of all three fields to propose theatre and performance as a public art form offering a mode of productive, robust engagement with the contemporary urban moment.